Carbapenem-resistant Pseudomonas aeruginosa infections in critically ill children: Prevalence, risk factors, and impact on outcome in a large tertiary pediatric hospital of China - Huang, Weichun; Wei, Xiaoshu; Xu, Guifeng; Zhang, Xingyu; Wang, Xing (Frontiers in Public Health, 2023)
Background and aims Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a major cause of healthcare-associated infections worldwide, but comprehensive study of clinical characteristics for CRPA infections among critically ill children remains limited in China. The objective of this study was to determine the epidemiology, risk factors, and clinical outcomes of CRPA infections among critically ill pediatric patients in a large tertiary pediatric hospital in China. Methods A retrospective case-control study of patients with P. aeruginosa infections was conducted in the three intensive care units (ICUs) of Shanghai Children's Medical Center from January 2016 to December 2021. All patients with CRPA infection in the ICUs were enrolled as case patients. Patients with carbapenem-susceptible P. aeruginosa (CSPA) infection were randomly selected as control patients in a ratio of 1:1. Clinical characteristics of those inpatients were reviewed through the hospital information system. Univariate and multivariate analyses were performed to evaluate risk factors associated with the development of CRPA infections and mortality of P. aeruginosa infections. Results A total of 528 cases of P. aeruginosa infection in the ICUs were enrolled in the 6-year study. The prevalence of CRPA and MDRPA (multidrug-resistance P. aeruginosa) was 18.4 and 25.6%, respectively. Significant risk factors related to CRPA infection were the length of hospitalization >28 days (OR = 3.241, 95% CI 1.622–6.473, p = 0.001), receiving invasive operations (OR = 2.393, 95% CI 1.196–4.788, p = 0.014) and a blood transfusion (OR = 7.003, 95% CI 2.416–20.297, p < 0.001) within 30 days before infection. Conversely, birth weight ≥2,500 g (OR = 0.278, 95% CI 0.122–0.635, p = 0.001) and breast nursing (OR = 0.362, 95% CI 0.168–0.777, p = 0.009) were significant protective factors against CRPA infections. The in-hospital mortality rate was 14.2%, and no difference in mortality was observed between patients with CRPA and CSPA infections. Platelet < 100 × 109/L (OR = 5.729, 95% CI 1.048–31.308, p = 0.044) and serum urea <3.2 mmol/L (OR = 5.173, 95% CI 1.215–22.023, p = 0.026) were independent predictors for the mortality due to P. aeruginosa infection. Conclusions Our findings provide insights into CRPA infections among critically ill children in China. They provide guidance in identifying patients that may be at high risk for a resistant infection and emphasize the importance of antimicrobial stewardship and infection control in hospitals.